FACTORS ASSOCIATED WITH THE SEVERITY OF PNEUMOCOCCAL PNEUMONIA IN CHILDREN AGED FROM 2 MONTHS TO UNDER 5 YEARS AT THE PEDIATRIC CENTER, THAI NGUYEN NATIONAL HOSPITAL, 2024–2025 (Vietnam Journal of Community Medicine, 2026)
Objective: To analyze several factors associated with the severity of pneumococcal pneumonia in children aged from 2 months to under 5 years at the Pediatric Center, Thai Nguyen Central Hospital during 2024–2025.Methods: A cross-sectional descriptive study was conducted on 153 children aged from 2 months to under 5 years who were diagnosed with community-acquired pneumococcal pneumonia at the Pediatric Center, Thai Nguyen National Hospital.Results: mean age of the children was 22.80 ± 14.88 months. Severe pneumonia accounted for 42.5% of cases. Children with a birth weight below 2,500 grams had a significantly higher rate of severe pneumonia compared with those whose birth weight was 2,500 grams or higher (72.2% vs. 38.5; p
Keywords: Severe pneumonia, pneumococcus, under five years, birth weight.